Career Construction as a Way to Promote Self-Determined Vocational Choices of People with Disabilities - Chang-kyu Kwon (Adult Education Research Conference, 2017)
The purpose of this round table is to discuss how transformative learning theory can be utilized to increase the quality of career development and vocational rehabilitation of people with disabilities.
Keywords: Transformative learning; people with disabilities; career development; vocational rehabilitation